2013
DOI: 10.1080/02791072.2013.805980
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Alcohol Use Among Monoracial and Biracial Black Adolescents and Adults

Abstract: Objective The present study investigates developmental trajectories of alcohol use from early adolescence to adulthood by age and race/ethnicity among White, Black, Black-American Indian, Black-Hispanic, and Black-White individuals and associated sociodemograhphic correlates. Method We used a subsample of nationally representative data obtained from the National Longitudinal Study of Adolescent Health (Add Health). The analytic sample consisted of 15,278 individuals in Wave 1 (ages 11 to 21 years). The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
2
24
1
Order By: Relevance
“…Third, prior research has indicated that substance use peaks when adolescents/young adults reach the 20s (Chen and Jacobson, 2012), and thus there are likely further fluctuations in substance use as YMSM continue to age. In addition, we note that the existing data show the potential for crossover effects of racial/ethnic differences in substance use levels (Chen and Jacobson, 2012; Clark et al, 2013; Finlay et al, 2012). Thus, the trajectories noted here should not be extrapolated beyond the 18 months of follow-up analyzed.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Third, prior research has indicated that substance use peaks when adolescents/young adults reach the 20s (Chen and Jacobson, 2012), and thus there are likely further fluctuations in substance use as YMSM continue to age. In addition, we note that the existing data show the potential for crossover effects of racial/ethnic differences in substance use levels (Chen and Jacobson, 2012; Clark et al, 2013; Finlay et al, 2012). Thus, the trajectories noted here should not be extrapolated beyond the 18 months of follow-up analyzed.…”
Section: Discussionmentioning
confidence: 85%
“…Conversely, Black YMSM demonstrated the lowest trajectories of alcohol use. Data from Add Health has indicated greater levels of alcohol use among White youth (Chen and Jacobson, 2012; Clark et al, 2013; Dermody et al, 2014), and prior data from New York City has indicated similar findings among YMSM (Halkitis et al, 2012). We note that the differences in trajectories found in the present study were attributable to the intercepts rather than the slopes.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…During young adulthood, the advantageous lower rates of substance use found in Black adolescents are lost and their rates of substance-use become comparable to their White and Hispanic counterparts (Clark, Corneille, & Coman, 2013; Geronimus, Neidert, & Bound, 1993). Although the causes of this phenomenon, referred to as the “catch-up effect,” are unknown, perceived discrimination may be an important predictor of the catch-up effect.…”
Section: Introductionmentioning
confidence: 99%